Analisis Perubahan Penggunaan Lahan di Kabupaten Sukoharjo dengan Menggunakan Metode NDVI Tahun 2013 dan 2023 - Amalia, Dika Fitri; Hijrawadi, Sony Nugratama (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2024)
Cities are places of life and centers of various human activities. The increasing population density and human needs for land use can certainly reduce the density of existing vegetation. This land use change can affect green cover in Sukoharjo Regency. Therefore, it is necessary to analyze land use change from the level of vegetation density in Sukoharjo Regency in 2013 and 2023 using the NDVI (Normalized Difference Vegetation Index) method. The use of digital remote sensing data, namely Landsat 8 image data, makes it possible to determine the distribution of vegetation density in each type of land use. The object of this research is vegetation density within 10 years, namely in 2013 and 2023 in Sukoharjo Regency. The variables of this research include vegetation density with NDVI values in Sukoharjo District in 2013 and 2023 and changes in vegetation density in Sukoharjo District. According to the results of the interpretation of Landsat 8 images, in 2013 and 2023 transformed with NDVI and classified into 5 classes of vegetation density, it is known that in 2013-2023 in Sukoharjo District there were changes in vegetation density in each class.